Individual versus Parental Consent in Marriage: Implications for Intra-Household Resource Allocation and Growth - Edlund, Lena; Lagerlöf, Nils-Petter (American Economic Review, 2006)
Individual versus Parental Consent in Marriage: Implications for Intra-Household Resource Allocation and Growth by Lena Edlund and Nils-Petter Lagerlöf. Published in volume 96, issue 2, pages 304-307 of American Economic Review, May 2006